Ocorrência de migrânea, cefaléia do tipo tensional e cefaléia em salvas em estudantes de medicina da universidade federal do Pará - FARIAS, Diego Costa (2022)
The headaches are between the main diseases that cause disability, with high implication on life quality, and they consist practically in an universal experience, with high prevalence in lifetime. This work has the objective of establish the occurrence of migraine, tension-type headache and cluster headache among medicine students of the Federal University of Pará. For that, it was used an individualized questionnaire with opened and closed questions, and the diagnosis was based on the diagnostic criteria of the second edition of the International Classification of Headache Disorders. The occurrence of the primary headaches in the studied sample was 56,7% (170/300), which 33,7% (101/300) belongs to the migraine group, 21,0% (63/300) belongs to the tension-type headache, and 2,0% (6/300) to the cluster headache group. It’s concluded that the primary headaches present a major occurrence between the medicine students of the Federal University of Pará, which deserve special attention for being exposed to a number of trigger and aggravating factors for primary headaches, and because of these ones have considerable impact as much in the general life quality as in the academic life.